The minimal magnified: Spain in The Glass Menagerie = Cuando lo mínimo se magnifica: España en El zoo de cristal - Suárez-galbán, Eugenio (Estudios Ingleses de la Universidad Complutense, 2004)
Critics have by and large ignored the role of Spain in Tennessee Williams’ The Glass Menagerie. At most, the few allusions to Spain and its Civil War in the play have traditionally been interpreted as simply designating a dramatic space and time that would contrast with the United States of the thirties. While this already implies a criticism due to said contrast between a complacent nation and one struggling for ideological survival, closer scrutiny of Williams’ text reveals a concomitance between Spain and the Wingfield family which sharpens and deepens even more the criticism against the attitude and role assumed by the United States and the West in general with respect to the Spanish Civil War. This, in turn, revives the polemic of Williams as a social writer, rather than one merely and mostly interested in the plight of the individual.
Keywords: Tennessee Williams; American drama; Spanish Civil War; The Glass Menagerie